Kualitas Produk dan Keragaman Produk Sebagai Determinan Kepuasan Konsumen - Dede Abdurahman; Dana Dana; Asep Sulaeman; Dede Solihin (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study is motivated by the importance of product quality and product variety in creating customer satisfaction in retail businesses. Toko Yan Curug, as a store serving consumers’ daily needs, needs to understand the factors that can improve customer satisfaction in order to maintain loyalty and business competitiveness. The purpose of this study is to analyze the role of product quality and product variety as determinants of customer satisfaction at Toko Yan Curug. The research method used is a quantitative approach with a survey technique through questionnaires distributed to 100 respondents who are customers of Toko Yan Curug. The sampling technique applied is accidental sampling, while data analysis is conducted through validity testing, reliability testing, multiple linear regression, and hypothesis testing. The results indicate that product quality and product variety play a positive role in shaping customer satisfaction, both partially and simultaneously. These findings confirm that customers tend to feel more satisfied when the available products have good quality and diverse choices that meet their needs.